Problematika Pembelajaran Sejarah Kebudayaan Islam di MTs Dhuafa Nusantara Padang - Nisa, Fadhila Khairatun; Ikhlas, Al (ALSYS, 2025)
The learning process will not always run smoothly, of course, there will be various problems or problems faced by both teachers and students in a school. As problems will hinder the learning process and results, these problems must be classified and should be resolved, especially for grade 7 students in SKI subjects at MTs Dhuafa Nusantara Padang. Based on observations, researchers found boredom experienced by students in learning. This study aims to determine the problematics of 7th grade SKI learning in SKI subjects. This research is descriptive qualitative type. The data sources used by the author are informants and documents. The instruments in this study were observation sheets and interview guidelines. Data collection techniques in the form of observation, interviews and documentation. The analysis technique applied is data collection, data reduction, data presentation and verification and the data validity technique used is source triangulation. The results showed that the problems faced by teachers included difficulties in planning methods, media and materials and efforts presented in the form of motivation both before and after learning, creating a fun and challenging learning atmosphere.